Trade links : new rules for a new world / James Bacchus. - Bacchus, James (Cambridge University Press, 2022)
The World Trade Organization is undergoing an existential crisis. Trade links the world not only through the flow of international commerce in goods, services, and ideas; but also through its economic, environmental, and social impacts. Trade links are supported by a WTO trading system founded on rules established in the 20th century which do not account for all the modern changes in the global economy. James Bacchus, a founder of the WTO, posits that this global organization can survive and continue to succeed only if the trade links among WTO members are revitalized and reimagined. He explains how to bring the WTO into the twenty-first century, exploring the ways it can be utilized to combat future pandemics and climate change and advance sustainable development, all while continuing to foster free trade. This book is among the first to comprehensively explain the new trade rules needed for our new world.